PENGARUH LINGKUNGAN KERJA FISIK DAN LINGKUNGAN KERJA NON FISIK TERHADAP KEPUASAN KERJA KARYAWAN PADA PT.PLN (PERSERO) WILAYAH SUMATERA SELATAN - I Ilhamsyah; Hj. Maliah (JURNAL KOMPETITIF, 2020)
This research aims to determine the influence of physical work environment and non-physical work environment to employee satisfaction at PT. PLN (Persero) South Sumatera region. Sampelyang used in this study is all employees of PT. PLN (Persero) region of South Sumatra which amounted to 82 people. The techniques in this study use methods in the form of data and numbers with a desktiptive approach that is to formulate and interpret data and numbers. As for the variables in this study is the physical work environment (X1) of the Non physical work environment (X2) and the bound variable (devenden) called the variable Y. Variable Y In this research work satisfaction. Data processed using software SPSS 23 for windows to produce a physical work environment to job satisfaction indicates that the value of T 4.944 significantly 0,000 < 0.05. Non Physical work environment variable on work satisfaction T value of 6.297 with significant 0,000 < 0.05. The hypothesis Examiner (test F) jointly 0,000 < 0, 05meaning that Ho is received, it can be concluded that there is a significant influence between a variable of physical work environment and a non-physical work environment to employee work satisfaction at PT. PLN (Persero) South Sumatera region. Keywords: Environment Workworswork, Environment Non-Physical Work, Content work